Analisis Peran Penyuluh Pertanian dalam Pengembangan Usaha Tani Jambu Mete (Studi Kasus: Kelurahan Watulea, Kecamatan Gu, Kabupaten Buton Tengah) - Yusran, Muhammad; Sahusilawane, Aphrodite M; Damanik, Inta P N (Jurnal Agrosilvopasture-Tech, 2025)
The objective of this research was to analyze the role of agricultural extension worker in developing cashew farming in Watulea Village, Gu District, Buton Tengah Regency based on productivity of cashew farm that still in low category, whereas this village is one of the cashew production centers in Sulawesi Tenggara Province. There were various problems faced by cashew farmers which require the presence of agricultural extension workers as mentor, facilitator and organizer. Respondents were 60 cashew farmers representing 120 cashew farmers in this area and were taken at simple random sampling using lottery numbers from a list of names of all cashew farmers. Primary data was collected through structured interview with respondents using questionnaires; while secondary data was collected from various literature sources and related agencies such as the local village head's office. Data analysis was carried out descriptively qualitatively using data tabulation and preparing intervals for each research variable based on the highest value (score) and the lowest value (score). The result showed that according to farmers' assessment, the three roles of extension worker have been carried out well, there were only a few indicators in the role of instructor that still need to be improved, namely training farmers to choose and use medicines to prevent and control pests and diseases as well as fertilizers appropriately. Also developing ideas or concepts and putting them into practice to motivate farmers to develop farming businesses. As facilitator, extension workers have been considered good by farmers, as well as as organizer.